Fungi-Induced Upper and Lower Respiratory Tract Allergic Diseases: One Entity - Barac, Aleksandra; Ong, David S. Y.; Jovancevic, Ljiljana; Peric, Aleksandar; Surda, Pavol; Tomic Spiric, Vesna; Rubino, Salvatore (Frontiers in Microbiology, 2018)
Introduction: Aspergillus can cause different allergic diseases including allergic bronchopulmonary aspergillosis (ABPA) and allergic fungal rhinosinusitis (AFRS). ABPA is allergic pulmonary disease against Aspergillus antigens. AFRS is a type of chronic rhinosinusitis (CRS) presented as hypersensitivity reactions to the fungal presence in sinuses. The aim of the present study was to clarify if ABPA and AFRS could be considered as a common disease entity. Methodology: The prospective cohort study included 75 patients with ABPA. Patients were divided into two groups and compared with each other: (i) patients with CT confirmation of rhinosinusitis and presence of fungi in sinuses (ABPA+AFRS group) and (ii) patients without CT or without mycological evidence of AFRS (ABPA group). Results: Findings of this study were: (i) AFRS was confirmed in 80% of patients with ABPA; (ii) all ABPA+AFRS patients had allergic mucin while fungal hyphae were present in 60% sinonasal aspirate; (iii) ABPA+AFRS patients had more often complicated CRS with (nasal polyps) NP (p < 0.001) and more severe forms of CRS; (iv) culture of sinonasal aspirate revealed fungal presence in 97% patients with ABPA+AFRS; (v) patients with ABPA+AFRS had more common positive skin prick test (SPT) for A. fumigatus (p = 0.037), while patients without AFRS had more common positive SPT for Alternaria alternata and Penicillium notatum (p=0.04 and p=0.03, respectively); (vi) 67% of ABPA patients had Aspergillus induced AFRS; (vii) larger number of fungi was isolated from the air-samples obtained from homes of patients with ABPA+AFRS than from the homes of patients without AFRS, while the most predominant species were A. fumigatus and A. niger isolated from almost 50% of the air-samples. Conclusion: The pathogenesis of ABPA and AFRS is similar, and AFRS can be considered as the upper airway counterpart of ABPA. Fungi-induced upper and lower respiratory tract allergic diseases present common entity. Next studies should clarify the mechanism by which fungi turn from ‘normal flora’ into the trigger of immunological reactions, resulting in ABPA or AFRS as well as to find new approaches for its’ diagnosis and treatment.